2021
DOI: 10.7554/elife.63056
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptomic taxonomy of Drosophila circadian neurons around the clock

Abstract: Many different functions are regulated by circadian rhythms, including those orchestrated by discrete clock neurons within animal brains. To comprehensively characterize and assign cell identity to the 75 pairs of Drosophila circadian neurons, we optimized a single-cell RNA sequencing method and assayed clock neuron gene expression at different times of day. The data identify at least 17 clock neuron categories with striking spatial regulation of gene expression. Transcription factor regulation is prominent an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

55
210
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(265 citation statements)
references
References 56 publications
55
210
0
Order By: Relevance
“…3 E ), coupled with its fast evolution (i.e., the high d N , fig. 3 C ) and expression in the clock-neurons ( Ma et al 2021 ) may be associated with divergence in the circadian clock in species with different ecology and latitudinal distribution ( Menegazzi et al 2017 ). This might explain the findings in the agricultural pest D. suzukii , a species characterized by significant selective pressure affecting Rh6 and Rh7 ( fig.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…3 E ), coupled with its fast evolution (i.e., the high d N , fig. 3 C ) and expression in the clock-neurons ( Ma et al 2021 ) may be associated with divergence in the circadian clock in species with different ecology and latitudinal distribution ( Menegazzi et al 2017 ). This might explain the findings in the agricultural pest D. suzukii , a species characterized by significant selective pressure affecting Rh6 and Rh7 ( fig.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…The absorbance of Rh7 is particularly broad with a maximum in the UV light, but with a long tail encompassing the blue and cyan wavelengths ( Sakai et al 2017 ). Rh7 is expressed in a limited number of neurons in the central brain, including some of those responsible for circadian activity ( Ni et al 2017 ; Ma et al 2021 ). Rh2 is expressed in the ocelli ( Pollock and Benzer 1988 ) and possibly in the R7 photoreceptor cells.…”
Section: Introductionmentioning
confidence: 99%
“…We note that such a conclusion, based on negative results, would not have been possible with existing DN1p GAL4 lines. Recent studies have demonstrated that DN1p neurons are a heterogeneous group that can be further divided into multiple subpopulations that likely make distinct contributions to behavior ( Chatterjee et al., 2018 ; Guo et al., 2018 ; Lamaze et al., 2018 ; Ma et al., 2021 ). These findings indicate that a thorough understanding of the role of DN1p neurons in circadian control will require a fine-grained analysis of different DN1p subpopulations.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our dpr/DIP expression could serve as a map to identify individual MNs from a MN cluster in a larval VNC sample (Nguyen et al, 2021;Vicidomini et al, 2021). In addition to dprs and DIPs, other CSP subfamilies have been reported in several scRNAseq datasets, suggesting that expression maps of other subfamilies and even combinations of subfamilies can be utilized to refine cell types in datasets (Kurmangaliyev et al, 2020;Ma et al, 2021;Xie et al, 2021).…”
Section: Using the Dpr/dip Code To Annotate Single Cell Rna Sequencing Datamentioning
confidence: 95%